Projeto e desenvolvimento de um emulador de arranjo fotovoltaico utilizando um conversor CC-CC trifásico PWM - Viglus, Francisco José (2015)
This work presents a study, design, and development of a 4 kW photovoltaic array emulator. The emulator is composed of a power supply capable of delivering voltages and currents whose behavior resembles the behavior of a photovoltaic array. The structure of this power supply consists of a three-phase full-bridge DC-DC converter. This high frequency isolated converter provides a smaller volume and ensures safety for laboratory equipment. This work can be applied to test photovoltaic inverters with MPPT methods and dynamic responses up to 300Hz. The control strategy is based on the numerical solution of the mathematical model of a photovoltaic cell from which is extracted a reference current to the control of the emulator. The methodology applied to design the proposed power supply is also presented. Finally, the design, simulation, and practical results of the emulator are shown to prove its operation.